On the Effects of Linking Voluntary Cap-and-Trade Systems for CO2 Emissions - Martin L. Weitzman; Bjart J. Holtsmark (Center for Economic Studies and ifo Institute (CESifo), 2018)
Linkage of cap-and-trade systems is typically advocated by economists on a general analogy with the beneficial linking of free-trade areas and on the specific grounds that linkage will ensure cost effectiveness among the linked jurisdictions. An appropriate and widely accepted specification for the damages of carbon dioxide (CO2) emissions within a relatively short (say 5-10 year) period is that marginal damages for each jurisdiction are constant (although they can differ among jurisdictions). With this defensible assumption, the analysis is significantly clarified and yields simple closed-form expressions for all CO2 permit prices. Some implications for linked and unlinked voluntary CO2 cap-and-trade systems are derived and discussed.
Keywords: Q50; Q51; Q52; Q54; Q58; 330; linkage; cap and trade; pollution; climate change